The Role of Ergonomic Interventions to Prevent the Occurrence of Carpal Tunnel Syndrome in Dentists: - - Vallerie Trisha; Wita Anggraini; Indrani Sulistyowati; Annisaa Putri Ariyani; Dicha Yuliadewi Rahmawati (Majalah Biomorfologi, 2025)
Highlights Dentists are at a higher risk of experiencing symptoms of carpal tunnel syndrome (CTS) compared to non-dental healthcare workers. This is due to repetitive movements, the use of vibrating tools, and prolonged exposure to unergonomic postures. Ergonomic interventions are a key method for preventing CTS in dentists, aiming to reduce the risk of repetitive injuries that can lead to long-term disability.   Abstract Background: Carpal tunnel syndrome (CTS) is a peripheral mononeuropathy caused by compression of the median nerve. Dentists are susceptible to CTS due to awkward static body postures and ergonomic issues with the wrist, including the use of vibrating instruments, repetitive movements, large muscle forces, and awkward postures such as flexion, extension, and ulnar and radial deviation. Objective: This study aimed to review various studies on ergonomic interventions to prevent CTS in dentists. Material and Method: This research followed PRISMA-ScR guidelines and used PCC framework (Population, Concept, and Context) for article selection process. Inclusion criteria consisted of articles with an experimental research design published between 2011 and 2021. Exclusion criteria included scoping reviews, rapid reviews, systematic reviews, gray literature, and articles that were not fully accessible. All keywords were taken from MeSH terms, and literature searches were conducted using Boolean searches on the PubMed, Wiley, and Google Scholar databases on August 17, 2021. Result: There were limited experimental research articles on CTS in dentists. Out of 887 articles obtained, only five were selected, with a total of 357 participants. The research subjects included general dentists, specialist dentists, and dental hygienists, both with and without CTS. Conclusion: Ergonomic interventions play a crucial role in preventing CTS in dentists. Clinically, these interventions are associated with improved hand function, reduced pain in the wrist/hand, and increased pinch and grip strength.